Turbina tipa Saxo - kombinacija cevne in Kaplanove turbine - Höfler, Edvard (Acta hydrotechnica, 2000)
During the last decade in Canada, a turbine of the Saxo type has become a well-recognised product of Litostroj. Saxo is a vertical axial turbine whose construction between the turbine inflow and the runner is similar to tubular turbines with an inlet elbow and semi-axial i.e., conical guide apparatus. Between the runner inlet and the turbine outflow it is similar to conventional Kaplan turbines. This turbine is suitable for covering both operating ranges of Kaplan and tubular turbines. In this paper we describe theadvantages of the design and the hydrodynamic characteristics of the Saxo-turbine. The resultsof the theoretical and numerical investigations of the flow field in the distributor and runner regions are presented. The advantage of the semi-axial distributor is its capability for generating a slightly forced vortex flow, due to which the velocity distribution ahead of the runner blading becomes more uniform. Numerical analysis helped us in identifying the regions of unsatisfactory flow conditions that might be potential sources of power losses and cavitation
Keywords: cevne vodne turbine; construction; flow conditions; gonilniki; guide apparatus; konstrukcija; runner; tokovne razmere; vertical tubular hydro turbine; vertikalne cevne vodne turbine; vodilniki